Revisiting Quadrature, Infinity, and the Numbers - Soldatos, Gerasimos T. (Research Highlights in Mathematics and Computer Science Vol. 9, 2023)
Potential infinite consists of the potential infinite of the decimal digits that might start being added at the end of a given rational endlessly, and by the potential infinite of the order/disorder with which decimal digits would keep piling up. The infinite division of polygon sides must have an end if the points comprising a circle circumference and not thin air, a complete vacuum, is to be produced. Consequently, the decimal digits of \(π\) must have an end. The numerator is always a prime number while the denominator is always a multiple of four nearest to the numerator.